Phytoremediation of Petroleum Hydrocarbon by Micro Green Algae: A Review - Assim H. Flayyih; Buthena A. AL Magdamy (مجلة مركز بحوث التقنيات الاحيائية)
Background: The Industrial Revolution included processes of extracting, refining, and transporting oil and fossil fuels, as well as the increased demand for liquid oil worldwide, which has led to unprecedented pollution processes and the significant spread of pollutants. This led us to stop and think about the methods of treating pollutants that affect all forms of life, whether human, animal, or plant. Treatment must be at the lowest cost and environmentally friendly, such as the use of green technology by using many living organisms, including green algae, which participate indirectly in the breakdown of hydrocarbon compounds by activating mechanisms ranging from attack through the release of free radicals or the production of enzymes capable of decomposing hydrocarbons. Or by using organic carbon derived from hydrocarbon compounds as a food source for algae. Pollutants can also be removed by bioaccumulation outside or inside the algae cell body. The following review presents an analysis of published works available in the last ten years related to the ability of green microalgae to remove hydrocarbons with the aim of identifying alternative technology in these microorganisms for the use of bacteria and fungi. Aim of the study: The use of microorganisms in treating oil pollutants. Results: The best types of bacteria used in treatment are Marinobacter, Acinetobacter, Bacillus, Pseudomonas, Neptunomonas, Alcanivorax, Cycloclasticus, and Oleiphilus, while the most efficient microalgae species are Chlorella vulgaris and Scenedesmus spp. Conclusion: There is the possibility of using bacteria, fungi, and algae in bioremediation, but the best is algae because it is environmentally friendly and inexpensive.